2004
DOI: 10.4028/www.scientific.net/kem.270-273.1911
|View full text |Cite
|
Sign up to set email alerts
|

Impact Response and Damage of Composite Shell with Various Curvatures

Abstract: In this study, the impact responses and damage behaviors of CF/Epoxy(Carbon Fiber/Epoxy Resin) composite laminates have been studied considering the effects of various curvature radius. During the impact, the impactor's kinetic energy is consumed by the rebound energy of the impactor, strain energy and damage energy. Most of the kinetic energy is consumed by delamination propagation including crack growth. Therefore the contact force-time and deflection-time histories were measured to determine the specimen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Results indicated that the contact force increases and the amplitude of shell response decreases with decrease in shell radius. Similar results were observed in the studies of Leylek et al [12] and Kim and Yang [13] and confirmed with the nonlinear finite element analysis. Moody et al [15] experimentally studied the effects of specimen width and curvature on the residual compression strength of composite sandwich panels after low energy impact.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results indicated that the contact force increases and the amplitude of shell response decreases with decrease in shell radius. Similar results were observed in the studies of Leylek et al [12] and Kim and Yang [13] and confirmed with the nonlinear finite element analysis. Moody et al [15] experimentally studied the effects of specimen width and curvature on the residual compression strength of composite sandwich panels after low energy impact.…”
Section: Introductionsupporting
confidence: 92%
“…These papers show that the majority of published work has focused on impact of plates rather than curved structures. The detailed studies on the curved composite laminates have been seen after the 1990s [415]. Ambur and Starnes [9] showed that the plate radius and plate thickness were important structural parameters that influence the nonlinear response of a plate for a given impact energy.…”
Section: Introductionmentioning
confidence: 99%